Gas and liquid-fuelled HVOF spraying of Ni50Cr coating: microstructure and high temperature oxidation - Song, B.; Pala, Z.; Voisey, K.T.; Hussain, Tanvir (Elsevier, 2016)
Ni50Cr thermally sprayed coatings are widely used for high temperature oxidation and corrosion in thermal power plants. In this study, a commercially available gas atomised Ni50Cr powder was sprayed onto a power plant alloy (ASME P92) using both gas and liquid fuelled high velocity oxy-fuel (HVOF) thermal spray. Microstructures of the two coatings were examined using SEM-EDX, XRD, oxygen content analysis and mercury intrusion porosimeter. The gas fuelled coating had higher levels of oxygen content and porosity. Shorter term air oxidation tests (4 h) of the free-standing deposits in a thermogravimetric analyser (TGA) and longer term air oxidation tests (100 h) of the coated substrates were performed at 700 °C. The kinetics of oxidation and the oxidation products were characterized in detail in SEM/EDX and XRD. In both samples, oxides of various morphologies developed on top of the Ni50Cr coatings. Cr2O3 was the main oxidation product on the surface of the coatings along with a small amount of NiO and NiCr2O4. Rietveld analysis was performed on the XRD data to quantify the phase composition of the oxides on both Ni50Cr coatings and their evolution with exposure time.